Inactivation of non-toxigenic and toxigenic Escherichia coli O157:H7 inoculated on minimally processed tomatoes and cucumbers: Utilization of hydrosols of Lamiaceae spices as natural food sanitizers - Sagdic, Osman; Ozturk, Ismet; Tornuk, Fatih (ELSEVIER SCI LTD, 2013)
Hydrosols obtained from three Lamiaceae plants (thyme, summer savory and oregano) were evaluated for their antibacterial activity against two Escherichia coli O157:H7 strains inoculated to fresh-cut tomato and cucumbers. Complete inhibitions of both E. coli O157:H7 strains on fresh-cut tomato and cucumber were achieved by all hydrosol treatments in varying treatment periods for low inoculation level (10(4) cfu/mL) while water wash (control) was inefficient to eliminate the bacterial populations. In the case of high inoculation (10(6) cfu/mL), hydrosol treatments reduced the populations to undetectable levels on cucumber cuts. Moreover, reductions in E. coli O157:H7 populations of fresh-cut tomato were always higher than 2.50 log cfu/g at this inoculation. The results suggested that hydrosols from Lamiaceae plants have the potential to be used as natural food sanitizers for fresh-cut tomatoes and cucumbers to provide their microbial safety without causing any sensorial defect on treated products or health problems in human. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Fresh-cut tomato; Cucumber; Decontamination; Escherichia coli O157:H7; Lamiaceae; Plant hydrosol; Minimal processing; PLANT ESSENTIAL OILS; THYME ESSENTIAL OIL; ANTIBACTERIAL ACTIVITY; SATUREJA-HORTENSIS; SALMONELLA-TYPHIMURIUM; ANTIMICROBIAL ACTIVITY; EFFICACY; OREGANO; O157-H7; PRESERVATION; Food Science & Technology